Manajemen Kurikulum dalam Pengendalian Mutu Lulusan di MTs Ilmu Al-Qur’an Mojokrapak Jombang - Wafa, M. Aliyul; Wijaya, Leony (ISLAMIKA, 2024)
Education is an important aspect of a country's development, this is because quality education has a big influence on improving the quality of human resources. In Indonesia itself, problems related to education are still homework for the Indonesian government, especially problems related to the quality of graduates. The quality of education graduates in Indonesia refers to the abilities and qualities possessed by students after carrying out and completing the learning process. In this way, the good quality of graduates shows the good quality of education. This research aims to determine Curriculum Management in Improving the Quality of Graduates at MTs Al-Quran Sciences Mojokrapak Jombang. The method used by researchers in this research is a descriptive qualitative method with primary and secondary data sources. The data collection procedures used in this research include observation, interviews and documentation. Qualitative techniques for analyzing survey data include data reduction, data presentation and drawing conclusions. The results of this research show that: (1) Curriculum planning at MTs Ilmu Al Qur'an Mojokrapak Jombang involves experts, school supervisors, existing stechholders, as well as all teacher councils and expert staff (2) Implementation of the curriculum in improving the quality of graduates at MTs Al Qur'an Science, Mojokrapak, Jombang, this is done by preparing the readiness of all components that will be involved in implementing the curriculum, such as teacher readiness in implementing the curriculum, and strategies for implementing the curriculum in improving the quality of graduates (3) Evaluation of the curriculum in improving the quality of graduates at MTs Al Qur'an -The Mojokrapak Jombang Qur'an is carried out periodically and routinely every mid-semester and end of the semester.